THE EFFECT OF JOB INSECURITY AND WORK STRESS ON TURNOVER INTENTION OF EMPLOYEES OF GARUDA RAJAWALI KONVEKSI YOGYAKARTA - Fitra Rahmi Fauzaan; Kiki Sudiana (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Competition in the garment manufacturing industry is becoming increasingly severe, and as a result, businesses are required to possess high-quality human resources who are capable of performing at their highest potential. On the other hand, circumstances such as job instability and high levels of stress at work can have an impact on the desire of employees to leave the organization (something known as turnover intention). The purpose of this study is to investigate the relationship between job insecurity and stress at work and the intention of employees at Garuda Rajawali Konveksi Yogyakarta to leave their current positions. The investigation makes use of a causal method in conjunction with a quantitative approach. All of the employees at Garuda Rajawali Konveksi Yogyakarta make up the study population. There were around 69 people that participated in the survey, and the information was collected through the use of purposive sampling. Distribution of questionnaires utilizing a Likert scale with five points was the method that was utilized to collect the data. SmartPLS 4.0 was utilized in order to carry out the data analysis. The findings of the study reveal that job instability has a positive and substantial impact on the intention of employees at Garuda Rajawali Konveksi Yogyakarta to leave their current position. The p-value for this effect is 0.003, which is less than the threshold of 0.05. Furthermore, it is worth noting that work stress has a positive and noteworthy impact on turnover intention, as evidenced by a p-value of 0.000 (which is less than 0.05). According to these findings, the desire of employees to leave their current employer increases in proportion to the degree to which they are worried about their jobs and the amount of stress they face on the job. Therefore, in order to lessen the likelihood of employees leaving the company, the corporation needs to improve the sense of job security that employees have and properly manage stress at work.